Franciscan Library and Museum with Pinacotheca in Ljubljana - Jan Dominik Bogataj (Clotho)
The Franciscan Museum and Pinacotheca of the Franciscan Friary in the center of Ljubljana represent, together with the renovated library, a newly conceived cultural and art-historical section of the Friary as the mother house of the Slovenian Franciscan Province of the Holy Cross. The library currently holds ca. 70,000 book units, including precious books such as incunabula – one-seventh of all incunabula in the country – and can thus boast the title of Slovenia’s most extensive monastic library. The newly designed museum showcases some of the friary’s key cultural and artistic objects.